2010
DOI: 10.1111/j.1365-2044.2010.06514.x
|View full text |Cite
|
Sign up to set email alerts
|

A paramedic study comparing the use of the Airtraq®, Airway Scope and Macintosh laryngoscopes in simulated prehospital airway scenarios*

Abstract: SummaryIn a randomised, cross-over study, we compared the use of the Airtraq Ò , Airway Scope and Macintosh laryngoscopes by paramedics for tracheal intubation in three simulated prehospital scenarios. Fifty-four paramedics were invited to take part. When evaluated in a difficult airway manikin, median IQR [range] 120] s; p < 0.0001). The success rate within 30 s was greater with the Airtraq (61%) and Airway Scope (93%) than with the Macintosh laryngoscope (22%; p < 0.0001). When used for a standard intubati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…This finding could explain, in part, the significant frequency of excessive dental pressure reported with the DLM including expert operators, as well as the higher ETI failure rate and longer ETI time for novices. Our findings on global satisfaction for the AWS confirm those of previous studies in inexperienced operators [7, 26, 27]. They also showed that DLM-ETI experts may rapidly appropriate the AWS-ETI technique.…”
Section: Discussionsupporting
confidence: 89%
“…This finding could explain, in part, the significant frequency of excessive dental pressure reported with the DLM including expert operators, as well as the higher ETI failure rate and longer ETI time for novices. Our findings on global satisfaction for the AWS confirm those of previous studies in inexperienced operators [7, 26, 27]. They also showed that DLM-ETI experts may rapidly appropriate the AWS-ETI technique.…”
Section: Discussionsupporting
confidence: 89%
“…We included 22 manikin studies (42 trials) . The Pentax AWS was more effective than the Macintosh laryngoscope for all outcomes except the rate of audible dental clicks or significant dental compression (equivalent to oral or pharyngeal injury in human studies, Table ).…”
Section: Resultsmentioning
confidence: 99%
“…An example of this is a recent study by Trimmel [110] comparing out-of-hospital intubation success rates of a conventional laryngoscope with those of the Airtraq Ò videolaryngoscope (King Systems, Noblesville, IN, USA) in the pre-hospital setting. Although the Airtraq has been demonstrated to be effective in elective patients in the operating theatre [111][112][113][114], in the pre-hospital setting anaesthesia trained emergency physicians achieved only 49% successful tracheal intubation with the Airtraq, whereas conventional laryngoscopy was successful in 99%. Moreover, in 54 of 56 patients where Airtraq intubation failed, direct laryngoscopy was successful on the first attempt.…”
Section: Intubation Through a Sadmentioning
confidence: 99%